KEADILAN, TATA KELOLA, DAN KEBERLANJUTAN: KERANGKA SPAB DALAM REFORMASI AGRARIA MODERN - Muhamad Rafi Akbar Maulana; Rezza Fauzi Muhammad Fahmi; Muhammad Fiqri Fauzan; Muhammad Rouf Habiballoh (KRONIK : Journal of History Education and Historiography, 2026)
In this article, we discuss the role of Land-Based Agrarian Reform Schemes (LRAs) in promoting agrarian justice, governance, and sustainability in Indonesia. We focus on tenure conflicts, land tenure inequality, and the lack of protection for vulnerable groups. The objectives are as follows: (1) to explain the role of LRAs in the current agrarian reform agenda; (2) to explain the essential components that underpin substantive and procedural justice in agrarian management; and (3) to identify factors that determine the success and failure of LRAs implementation at the local level. Qualitative-descriptive methods are used through literature studies, policy reviews, and comparative analyses of relevant local practices. Data are collected through thematic analysis of regulatory documents, program reports, academic publications, and secondary field findings. The analysis focuses on the interactions between actors, institutional capacities, participation mechanisms, and the socio-political context that shapes LRAs implementation. The results show that LRAs can represent rights and distribute resources if supported by appropriate tenure maps, significant participation, transparency, and sustained support. However, this success is not evenly distributed. This "false compliance" can lead to the marginalization of vulnerable groups due to limited institutional capacity, dominant local elite interests, low accountability, and a lack of conflict resolution mechanisms. These findings suggest that policy outcomes do not automatically equate to equity at the grassroots level; configurations of power and social legitimacy are often more powerful. According to this article, for SPAB to function as a driver of just and sustainable agrarian reform, improved governance, increased implementation integrity, and inclusive participatory design are required.